Validasi Instrumen “In-Store Logistics” Dalam Kontek Pasar Tradisional - Moh Farid Najib (Politeknik Negeri Bandung, 2018)
In-store logistics guarantees product availability, product availability plays a major role for retail activities, inthe absence of available products means no purchase transactions. However, the development of the size of instorelogistics has not been developed especially for traditional markets. Thus, this research aims to evaluate thein-store logistics scale from a traditional market in Bandung Indonesia. The purpose of this research is to evaluatethe applicability of the in-store logistics scale in the context of traditional market in Bandung, Indonesia. A surveyhas been conducted toward 400 traders of traditional market in 14 traditional markets around Bandung,Indonesia. The findings are cross-validated hierarchically using both order confirmatory factor analysis andsecond order confirmatory factor analysis. The research finds that the in-store logistics structure is applicable inthe Indonesian Traditional Market setting. In addition, the result of the first order confirmatory factor analysis isshown that the dimension of in-store logistics correlation between construct and square variance extracted theseven sub-dimensions that consists of; stock, return, shopping equipment, product accessibility and information.Furthermore, the second order confirmatory analysis shown that the dimensions of in-store logistics scale consistof three dimensions (stock, return and shopping equipment).